2023
DOI: 10.1039/d2py01591a
|View full text |Cite
|
Sign up to set email alerts
|

Donor–acceptor Stenhouse adduct functionalised polymer microspheres

Abstract: Polymers that carry donor-acceptor Stenhouse adducts (DASAs) are a very relevant class of light-responsive materials. Capable of undergoing reversible, photoinduced isomerisations under irradiation with visible light, DASAs allow for on-demand...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…In addition to photoswitching from colored triene-2-ol to colorless cyclopentenone, a thermal reversion of the cyclized molecule back to the open-chain triene-2-ol conformation is very well-known in the solution phase. , However, similar to other photoresponsive molecules like azobenzene, spiropyrane, and diarylethene, the thermal reversion of DASA on the solid surfaces is limited due to intermolecular cohesive forces and still poses problems even today. , However, recent advances in the solid-state photoswitching of DASA reveal that the polymer design and molecular distribution can provide enough space for photoisomerization. Furthermore, a recent study of the Wang group revealed that the presence of an ester group influences the thermal reversion of cyclic colorless cyclopentenone to open-chain colored triene-2-ol on solid surfaces, which coincide well with the inherent ester functionality of the OrmoComp chemical system.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to photoswitching from colored triene-2-ol to colorless cyclopentenone, a thermal reversion of the cyclized molecule back to the open-chain triene-2-ol conformation is very well-known in the solution phase. , However, similar to other photoresponsive molecules like azobenzene, spiropyrane, and diarylethene, the thermal reversion of DASA on the solid surfaces is limited due to intermolecular cohesive forces and still poses problems even today. , However, recent advances in the solid-state photoswitching of DASA reveal that the polymer design and molecular distribution can provide enough space for photoisomerization. Furthermore, a recent study of the Wang group revealed that the presence of an ester group influences the thermal reversion of cyclic colorless cyclopentenone to open-chain colored triene-2-ol on solid surfaces, which coincide well with the inherent ester functionality of the OrmoComp chemical system.…”
Section: Resultsmentioning
confidence: 99%
“…126 Analogously, N -phenylpropane-1,3-diamine was used to modify cross-linked poly(styrene- co -vinylbenzyl chloride) microspheres, which enabled the formation of third-generation DASAs. 127 Sulfonyl groups in poly(2-ethylsulfonyl-2-oxazoline) gels were substituted with N -ethyl-1,3-propanediamine or N -phenylethylenediamine to obtain secondary alkyl and aryl amines on the polymer (Fig. 10e).…”
Section: Dasa-containing Polymersmentioning
confidence: 99%
“…11) primarily reacted with furan adducts via the less nucleophilic aniline moiety during synthesis. 127 This is likely due to increased steric hindrance for units in closer proximity to the main styryl network. In addition, linker chemistry and rigidity can also dictate thermal or mechanical properties of a polymer.…”
Section: Dasa-containing Polymersmentioning
confidence: 99%
See 2 more Smart Citations